The Influence of Socio-demographic Factors on the Prevalence of Dental Caries among 12-Year-Old Children, Narathiwat Province - Tanupattarasorn, Jutarat; Eso, Mayuening; McNeil, Rhysa (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
Dental caries is the most prevalent oral health issue among school-aged children. If not detected and treated promptly, this leads to severe pain and infection, tooth loss, and more complicated and expensive treatments. This study aimed to determine the prevalence and risk factors associated with dental caries among 12-year-old children in Narathiwat Province. The outcome of the study was dental caries in 12-year-old children's permanent teeth. Frequency and percentage were used to describe the preliminary data analysis. Chi-squared test was used for univariate analysis. Logistic regression was used to investigate the association between factors and dental caries. Permanent teeth in 9,216 children were affected by dental caries at the rate of 37.7%. Gender, religion, residence, medical treatment rights, father's age, father and mother's occupation, father and mother's educational level, and children's periodontal condition were associated with dental caries. The performance of the model was acceptable according to the area under a receiver operating characteristic curve at 72.3%. Therefore, children should be required to participate in preventive measures such as health education regarding oral hygiene, dietary habits, and dental visits.